Economic Misery, Urbanization and Life Expectancy in MENA Nations: An Empirical Analysis - Ali, Amjad; Audi, Marc; Roussel, Yannick (International Journal of Economics and Financial Issues, 2021)
This paper has examined the effect of urbanization and economic misery on average life expectancy in selected MENA nations from 2001 to 2016. Panel ARDL has been used for reviewing the co-integration among the selected indicators. The causality of the variables has been analyzed by impulse response function and variance decomposition. The outcomes reveal that food availability has significant and positive relation with an average life expectancy. The outcomes show that environmental standards put significant and positive impact on average life expectancy. The outcomes reveal that economic misery has a significant and negative influence on average life expectancy in MENA nations. The findings reveal that urbanization puts significant and positive influence on average life expectancy. So, for improving the average life expectancy in MENA nations availability of food, household final consumption and the level of urbanization must be enhanced, whereas at the same time economic misery should be reduced. Keywords: Economic misery, urbanization, life expectancy JEL Classifications: E24, E31, P25, J17 DOI: https://doi.org/10.32479/ijefi.11650